A study of triathletes` race strategies in different competition environments - Zhao, J.; Wu, Y.; Zhang, J. (Heliyon, 2024)
What is known, sports performance is impacted by a variety of factors. While most people understand the importance of training, proper nutrition, and adequate rest, not as many recognize the impact of environmental factors on athletic performance. This paper investigates the race strategies of Chinese triathletes in different competition environments, with a focus on the performance of professional triathletes during the Olympic Distance Triathlon held in China between 2015 and 2021. Data from 984 athletes who competed in 26 races were analyzed to evaluate the sensitivity of the three splits of swimming, cycling, and running to overall triathlon performance under different temperature (low, normal, and high), altitude (low, normal, and high), and waters (sea, river, and still waters) conditions. Results show that the effects of the three split times on overall time vary across different environments. Cycling has the greatest impact on overall performance when the temperature is suitable (at low temperature, at normal temperature) and the altitude is suitable (at low altitude, at normal altitude). While running has the greatest impact in high-temperature and high-altitude environments. For female athletes, in river waters, swimming has a greater effect on overall performance than cycling, but less than running. These findings provide practical suggestions for athletes, coaches, and competition organizers to optimize training and race strategies based on specific environmental conditions.